Pendekatan Kontekstual: Suatu Pendekatan Alternatif Pembelajaran Sejarah Di Sekolah Menengah Atas - Nur’aeni Marta (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2015)
This article is reviews about contextual approach as an alternative approach to teaching history in high school. The Contextual approach of teaching history is not a new approach, but it needs to be reconsidered in order to improve the quality of teaching history in high school.The teaching of history was still dominated by conventional approach, which is more emphasis on the mastery of the material(essentialism). It is not relevance with the educational nature of history itself, that is to humanize humans. The Contextual approach is a new perspective that is based on the context of the situation, place, time and conditions of a real environment faced by students daily. The teaching of history with this approachmeant the teacher is able to relate and connect the material study with real-life conditions.